Pola Komunikasi Tradisi Mapag Toya Dalam Upacara Ngayu-Ayu - I Komang Ariana (Jayapangus Press, 2018)
Traditional communication pattern of Mapag Toya in Ngayu-ayu Ceremony in Desa Pakraman Sangkan Gunung is intrapersonal communication, communication that happens within oneself. Interpersonal communication interaction face to face between two or several people, the sender can deliver the message directly. Public communication shows a communication process in which the message conveyed by the speaker in face-to-face situations in front of a larger audience, and organizational communication. The two functions of communication are hermit function, social function, sacrificial function, purification function, unity function, religious function. The three meanings of communication are the meaning of verbal communication and nonverbal communication.